CONTRIBUIÇÃO PARA O ESTUDO DA TUBERCULOSE NO MUNICÍPIO DE SÃO PAULO. ASPECTOS EPIDEMIOLÓGICOS DO PROBLEMA - Nussenzweig, Israel; Certain, Diogenes Augusto (Arquivos da Faculdade de Higiene e Saúde Pública da Universidade de São Paulo, 1953)
The annual tuberculosis death rate in the Minicipality of São Paulo from 1900 to 1948 is of 128.63 per 100,000 population. Tuberculosis in this Municipality is in its epidemic phase and in the stage of stabilization. The continuous increase of the coefficients verified since 1920 could be explained among other facts, by the rural exodus. The non-resident mortality during the years from 1946 to 1948 increased by 10% the tuberculosis death rate in those years. The tuberculosis mortality rate in the Municipality of São Paulo from 1900 to 1948 is 8,01% of the general mortality. In opposition to what is generally observed, in the Municipality of São Paulo the mortality from tuberculosis observed in the Municipality of São Paulo of mortality from tuberculosis does not follow the decreasing of the general mortality. The tuberculosis death rate related to the general mortality is higher in the last two decades of the studied period. The tuberculosis mortality reaches the higher rates between the ages of 15 and 39 years; the highed rate is located around 25 years of age. Between 15 and 21 years of age the death is higher for women; in the other groups of age the opposite is observed.